Social Mobility in Goal! The Dream Begins (2005) : An Analysis of The Main Character’s Journey - Wahyu Andika Rustanto,; Wahyu Budi, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study investigates the theme of social mobility as portrayed in the film Goal! The Dream Begins, focusing on the life journey of the main character, Santiago Muñez. It aims to examine the character's experience of social mobility and identify the key factors that contribute to his transformation. Employing a qualitative descriptive method, this research adopts a sociological approach to literature, using Sorokin’s theory of social mobility as the analytical framework. The study closely analyzes selected dialogues from the film to uncover how Santiago’s background, personal ambition, talent in football, and support from key individuals influence his mobility. The findings indicate that Santiago undergoes upward vertical social mobility, reflected in his transition from a low-income, working-class background to a successful professional footballer. This shift demonstrates not only a rise in his economic standing but also a significant improvement in his social status. In the end, the film emphasizes that personal determination, available opportunities, and social connections are crucial in facilitating social mobility, particularly when sports serve as a channel for transformation.